2019
DOI: 10.1016/j.heliyon.2019.e01579
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic analysis for dental caries detection using an adaptive neural network architecture

Abstract: Objectives AI techniques have lifelong impact in biomedics and widely accepted outcomes. The sole objective of the study is to evaluate accurate detection of caries using feature extraction and classification of the dental images along with amalgamation Adaptive Dragonfly algorithm (DA) algorithm and Neural Network (NN) classifier. Materials and methods Here proposed caries detection model is designed for detecting the tooth cavities in an accurate manner. This methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The term deep learning convolutional neural network or deep neural network (DNN) refers to the application of an artificial neural network (ANN) with multiple layers to analyse visual imagery, assign importance (learnable weights and biases) to various aspects of the image, and distinguish one characteristic from another. 1 8 15 16 A DNN can perform pattern recognition of images without human intervention. Once the program is established, raw data is processed via non-linear activation functions from shallow to deeper layers; as the layers get deeper, the raw data is translated into characteristics matching the representation of raw data.…”
Section: Discussionmentioning
confidence: 99%
“…The term deep learning convolutional neural network or deep neural network (DNN) refers to the application of an artificial neural network (ANN) with multiple layers to analyse visual imagery, assign importance (learnable weights and biases) to various aspects of the image, and distinguish one characteristic from another. 1 8 15 16 A DNN can perform pattern recognition of images without human intervention. Once the program is established, raw data is processed via non-linear activation functions from shallow to deeper layers; as the layers get deeper, the raw data is translated into characteristics matching the representation of raw data.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the methods used in the study, SVMs showed the best performance for the detection of root caries, with an accuracy of 97.1%, precision of 95.1%, sensitivity of 99.6%, and specificity of 93.3%. Other approached have been proposed in literature by using features extracted from photographic color images 121 and x-ray images, 122 achieving similar results.…”
Section: Techniques Applied To Dentistrymentioning
confidence: 92%
“…105 Color matching 120 Radiography, [110][111][112]115 CBCT Images, 105,116 clinical/other types of data, [117][118][119][120] other image formats 113,114 ML techniques Disease identification Dental caries, 13,121,122 periodontal disease, [123][124][125][126][127] oral cancer, [128][129][130][131][132][133][134][135] dental pain, 136 oral malodour, 137 oral clefts detection. 138 Oral disease prevention 139 Radiography, 122 other image formats, 121,128,129 clinical/biological data 13,[123][124][125][126][127][130][131][132][133]…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…The use of 3D intraoral scanners (IOS) and corresponding software for oral disease detection and monitoring has proven potential [1][2][3][4][5] . There is increasing development in this area, both by companies that produce medical devices, and by researchers seeking improved devices and software that can support automated detection and objective monitoring of oral diseases such as caries, tooth wear and periodontal diseases either in a clinical setup or remotely [1][2][3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%